(untitled) (LACCEI, 2024)
The influence and performance of the different types of heat sinks are analyzed and determined, according to the results on percentage reductions of maximum distortions, maximum displacements and maximum drifts, identifying the one with the best performance. In addition, based on quantitative and qualitative research, informality in the construction process is investigated, determining the average number of existing informal homes, the causes of self-construction and, above all, the enormous vulnerability to telluric movements of structures that do not comply with earthquake resistant designs.